مستويات الاحتراق النفسي وعلاقتها بالاكتئاب - بوحارة, هناء (جامعة الوادي - University of Eloued, 2019)
تهــــدف الدراسة الحـالية إلى الكشف عن مستويــات الاحتراق النفسي وعلاقتها بالاكتئاب لدى أعــوان الحماية المدنية. لتحقيق أهداف الدراسة والإجابة على فرضياتها، تم الاعتماد على المنهج الوصفي واختيار عينة عشوائية طبقية من فئة الأعوان بمديرية الحماية المدنية وبعض وحداتها بمدينة عنابة. حيث طبق عليها مقياس الاحتراق النفسي ومقياس الاكتئاب في العمل. وبعدما جُمعت البيانات وأُجريت المعالجات الإحصائية عن طريق برنامج الرزمة الإحصائية للعلوم الاجتماعية ,توصلت الدراسة إلى النتائج التالية: - كلمـا زاد الإنهاك النفسي البدني كلما ازدادت شدة الإستجابة الاكتئابية لدى أفراد العينة. - كلما ازدادت سلبية العلاقات تجاه الآخرين في العمل كلما اشتدت الإستجابةالاكتئابية لدى أفراد العينة. - غياب مظاهر الدعم النفسي الاجتماعي في العمل يؤدي إلى استجابة اكتئابية عالية لدى أفراد العينة. Abstract:This study aims to reveal the levels of burnout and the relationship with depression among civil protection agents. To achieve the aims of the study and to answer to its hypotheses, one adopted the descriptive method one chose a real arbitrary sample of the category of the agents of the direction of civil protection and these units at the level of the wilaya of Annaba . The Burnout scale and depression scale were applied at work. After collecting and statistically analyzing data by SPSS v20 the study concluded the next results: - There is a direct relationship between psychological-physical exhaustion and Depression response among the participants. - There is a direct relationship between negative relations orientation to others in work place and Depression response among the participants. - Social and psychological support absence lead to high levels of Depression response among the participants.
لدى أعوان الحماية المدنية
مقال
Keywords: إحتراق نفسي إكتئاب إكتئاب في العمل أعوان الحماية المدنية; Burnout; depression; depression at work; civil protection agents